2010
DOI: 10.1038/jhg.2010.48
|View full text |Cite
|
Sign up to set email alerts
|

SPP1 promoter polymorphisms and glioma risk in a Chinese Han population

Abstract: SPP1 was found to be significantly upregulated in many kinds of malignant tumors, including gliomas. Considering that gene polymorphisms have been implicated in the development of gliomas, we performed an association study between SPP1 functional promoter region polymorphisms and glioma risk in a Chinese population. We found significant evidence of an association between SPP1 promoter polymorphisms and glioma risk. For the À155_156insG variant, the À155_156GG allele was found to be significantly associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…A different SNP, 155_156GG was found to be significantly associated with an increased risk of glioma. Cellular assays indicated that the transcriptional activity of the SPP1 promoter containing the −155_156GG allele significantly increased in glioma cells indicating that this variant of SPP1 promoter might influence the risk of glioma by regulating promoter activity (Chen et al, 2010). …”
Section: Regulation Of Opnmentioning
confidence: 99%
“…A different SNP, 155_156GG was found to be significantly associated with an increased risk of glioma. Cellular assays indicated that the transcriptional activity of the SPP1 promoter containing the −155_156GG allele significantly increased in glioma cells indicating that this variant of SPP1 promoter might influence the risk of glioma by regulating promoter activity (Chen et al, 2010). …”
Section: Regulation Of Opnmentioning
confidence: 99%
“…The search strategy retrieved 40 potential relevant studies and one study was identified through references. According to the inclusion and exclusion criteria, 11 studies [ 10 , 12 , 22 – 30 ]with full text were eligible for this meta-analysis and 30 studies were excluded. The flow chart of study selection is summarized in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We observed a consistently lower prevalence of G allele and GG genotype ( OPN -156G) in the DN group as compared to the T2D group. OPN -156G allele has been earlier found to have a significant association with lower diastolic function in patients with diabetes mellitus, lower risk of developing calcium urolithiasis, more rapid progression of Duchenne muscular dystrophy, susceptibility to oral squamous cell carcinoma, systemic lupus erythematosus, glioma, and T1D [ 15 , 17 , 21 , 22 , 23 , 24 , 25 ]. The increased OPN activity has been suggested to stimulate TGF-β and matrix deposition in mesangial cells, which could significantly contribute to pathophysiology of DN.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been suggested that OPN haplotypes instead of single nucleotide polymorphisms may be a better predictor of genetic susceptibility and will allow achieving more accurate results. A few recent studies have confirmed OPN haplotypes as modifiers of disease susceptibility in sarcoidosis, nephrolithiasis, pseudoxanthomaelasticum, gliomas, Crohn’s disease, and oral carcinogenesis [ 9 , 13 , 14 , 15 , 16 , 17 ]. In the present study we have investigated the association of three functional promoter gene polymorphisms C-443T, delG-156G, and G-66T and their haplotypes with the risk of DN in two independent cohorts of north Indian T2D patients.…”
Section: Introductionmentioning
confidence: 99%